Formation and Abundance of 5‐Hydroxymethylcytosine in RNA. Issue 5 (12th February 2015) - Huber, Sabrina M.; van Delft, Pieter; Mendil, Lee; Bachman, Martin; Smollett, Katherine; Werner, Finn; Miska, Eric A.; Balasubramanian, Shankar
Abstract RNA methylation is emerging as a regulatory RNA modification that could have important roles in the control and coordination of gene transcription and protein translation. Herein, we describe an in vivo isotope‐tracing methodology to demonstrate that the ribonucleoside 5‐methylcytidine (m5C) is subject to oxidative processing in mammals, forming 5‐hydroxymethylcytidine (hm5C) and 5‐formylcytidine (f5C). Furthermore, we have identified hm5C in total RNA from all three domains of life and in polyA‐enriched RNA fractions from mammalian cells. This suggests m5C oxidation is a conserved process that could have critical regulatory functions inside cells.